Comparative Analysis of Laboratory and Prototype Models of Pervious Concrete Mixes Containing Reclaimed Asphalt Pavement Aggregates. Issue 5 (May 2022) - Sahdeo, Surya Kant; R.N., G.D. Ransinchung; Debbarma, Solomon
Pervious concrete (PC) is lightweight concrete with higher porosity and permeability than conventional concrete, making it suitable for reducing storm-water runoff from pavements. Incorporating reclaimed asphalt pavement (RAP) aggregates as a replacement for natural aggregates will likely enhance the porosity and permeability of PC pavement mixes. This paper provides a comparative analysis of the influence of RAP in PC pavement mixes when prepared in two different conditions (laboratory and field). To simulate field conditions, a prototype model tank consisting of subgrade and reservoir layers and a PC slab was constructed. Studies showed that the compaction types and efforts affect the RAP-PC prototype slab and require 50% extra cement to achieve the recommended 28-day compressive and flexural strength of PC pavements. The prototype model tank's surface infiltration (SI) test demonstrated a higher permeability but less density than laboratory-prepared specimens, indicating that the use of binary graded RAP aggregates contributes to a porous network structure, which improves the transport properties of PC pavement mixes. A correlation with a high R 2 value between the laboratory and prototype model tank was also established, indicating the coexistence of a relationship between the density and porosity of laboratory and Prototype-PC pavement mixes. Interestingly, it was reported that the use of standard proctor hammer compaction to cast laboratory specimens produced the same effect when the vibratory hammer compacted the RAP-PC prototype for 20 s. It is, therefore, recommended that 25% to 50% of RAP be used as a coarse aggregate replacement to produce PC pavement mixes.